Development and Evaluation of the Effectiveness of Serial Image Learning Media to Improve Narrative Writing Skills in 4th Grade Students - Nur Aripa Hasanah; Riris Nurkholidah Rambe (Journal of Social, Humanity, and Education, 2026)
Purpose: This study aimed to develop and evaluate serial picture learning media to improve the writing skills of fourth-grade students in Indonesian. Research Methodology: A research and development (R&D) approach using the ADDIE model (analysis, design, development, implementation, and evaluation) was employed. The study was conducted at MIN 12 in Medan City, involving 25 fourth-grade students (13 males and 12 females). Data were collected using validation questionnaires from material and media experts, teachers, and students to assess the validity and practicality of the developed media. Pretest and posttest instruments were administered to measure the effectiveness of the media. Results: Validation results showed that the serial picture learning media was highly feasible, with scores of 92% from material experts and 95% from media experts. The teacher and student practicality assessments were 91.5% and 93.38%, respectively, both categorized as very practical. The effectiveness test revealed an 85.5% improvement, indicating the media's success in improving students' writing skills. Conclusions: The findings demonstrate that serial picture learning media is valid, practical, and effective in enhancing students' writing skills in Indonesian. Limitations: This study included only 25 students from a single class, which may affect the generalizability of the findings to other educational settings. Contributions: This study offers valuable insights for teachers to integrate visual learning media, particularly serial pictures, to support writing skills development in Indonesian language instruction.